Insight transformation of agrisymphony 2025 instagram account through the optimization of the repost feature - Meisykla, Rafilza; Santoso, Hudi; Dharmawan, Leonard (Lembaga Riset Mutiara Akbar, 2026)
Social media has become a key medium in digital communication strategies due to its ability to reach a broad and interactive audience. Instagram, through its repost feature, provides users with the opportunity to strengthen engagement and expand content reach. This study aims to analyze the role of the repost feature in increasing Instagram insights on the Agrisymphony 2025 account using the Uses and Gratifications Theory (UGT) and Digital Interactivity Theory perspectives. The research findings indicate that the repost feature has a significant influence on increasing reach, impressions, engagement, and follower growth. Theoretically, these results support the Uses and Gratifications Theory, which emphasizes the active role of users in choosing media to meet their needs for information, entertainment, and social interaction. Furthermore, Digital Interactivity Theory explains that reposts function as a form of user participation that strengthens two-way communication between accounts and audiences. Thus, the strategy of using reposts has proven effective in strengthening content performance and increasing audience loyalty on the Instagram platform.